2022
DOI: 10.3389/fpls.2022.1011859
|View full text |Cite
|
Sign up to set email alerts
|

Silicon enhances plant resistance to Fusarium wilt by promoting antioxidant potential and photosynthetic capacity in cucumber (Cucumis sativus L.)

Abstract: Fusarium wilt, caused by Fusarium oxysporum f. sp. cucumerinum (Fo), is a severe soil-borne disease affecting cucumber production worldwide, particularly under monocropping in greenhouses. Silicon (Si) plays an important role in improving the resistance of crops to Fusarium wilt, but the underlying mechanism is largely unclear. Here, an in vitro study showed that 3 mmol·l-1 Si had the best inhibitory effect on the mycelial growth of F. oxysporum in potato dextrose agar (PDA) culture for 7 days. Subsequently, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 57 publications
0
3
0
1
Order By: Relevance
“…Rice plants supplied with Si showed increased sucrose concentration in response to B. oryzae infection [ 38 ]. The expression of Calvin cycle-related genes such as those coding for fructose-1,6-bisphosphate aldolase, phosphate isomerase, sedoheptulose-1,7-bisphosphatase, glyceraldehyde-3-phosphate dehydrogenase, fructose-1,6-bisphosphatase, and RuBisCO was repressed in cucumber plants infected with Fusarium oxysporum [ 39 ]. However, the expression of the genes mentioned above increased and improved the pool of soluble sugars and the resistance of cucumber against Fusarium wilt for Si-supplied plants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rice plants supplied with Si showed increased sucrose concentration in response to B. oryzae infection [ 38 ]. The expression of Calvin cycle-related genes such as those coding for fructose-1,6-bisphosphate aldolase, phosphate isomerase, sedoheptulose-1,7-bisphosphatase, glyceraldehyde-3-phosphate dehydrogenase, fructose-1,6-bisphosphatase, and RuBisCO was repressed in cucumber plants infected with Fusarium oxysporum [ 39 ]. However, the expression of the genes mentioned above increased and improved the pool of soluble sugars and the resistance of cucumber against Fusarium wilt for Si-supplied plants.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, SOD, APX, CAT, and GR activities were greatest earlier in the B. maydis infection process while SOD, CAT, and GR activities were higher at the advanced stage of fungal infection. Other studies showed that Si can stimulate the enzymatic antioxidant metabolism of pathogen-challenged plants by restricting the oxidative stress caused by an excess of ROS associated with less lipid peroxidation in the infected cells [ 12 , 13 , 17 , 20 , 39 , 43 ]. In the present study, APX activity was higher for infected −Si plants in contrast to infected +Si plants from 60 to 156 hai, possibly due to the higher availability of H 2 O 2 that needed detoxification.…”
Section: Discussionmentioning
confidence: 99%
“…Aplikasi silika mampu meningkatkan kandungan fenol, flavonoid, lignin, dan dopamin (Fortunato et al 2014) atau menginduksi pembentukan enzim, hormon dan senyawa anti jamur berupa aglikon dan fitoaleksin yang dapat meningkatkan resistensi tanaman (Ahammed dan Yang 2021) terserang penyakit, sehingga meskipun telah terinfeksi kerusakannya akan rendah. Penggunaan silika mampu menghambat serangan bercak ungu bawang merah (Hersanti et al 2019), busuk akar putih bawang merah (Elshahawy et al 2021), dan fusarium pada tanaman pisang (Fortunato et al 2014) dan mentimun (Sun et al 2022).…”
Section: Hasil Dan Pembahasan Intensitas Penyakit Dan Laju Infeksiunclassified
“…It is not yet considered an essential nutrient but has proved to play an extensive plant-growth-promoting role, particularly in stress conditions [ 23 , 25 ]. The role of Si application in mitigating or neutralizing harmful effects has subsequently been disclosed for several stresses, including temperature [ 26 ], salinity and drought [ 25 , 27 ], heavy metals stress [ 28 ], and diseases in plants [ 29 ]. Additionally, it is also known for playing a vital role in improving nutrient deficiencies in plants, including potassium [ 30 ] and iron [ 31 ].…”
Section: Introductionmentioning
confidence: 99%